Accessibility and proximity effects of bus rapid transit on housing prices: Heterogeneity across price quantiles and space. (October 2020) - Yang, Linchuan; Chu, Xiaoling; Gou, Zhonghua; Yang, Hongtai; Lu, Yi; Huang, Wencheng
Abstract: Bus rapid transit (BRT) systems have mushroomed worldwide in the last few decades. An enriched understanding of BRT capitalization effects is essential. Although the BRT accessibility effect on housing prices has been extensively explored, the effect of proximity to the BRT corridor (which may be related to unattractive landscape and noise pollution) has been little scrutinized. More importantly, whether and how the two effects vary across price levels and space have yet to be sufficiently studied. To this end, we estimate the effect of BRT accessibility and proximity on housing prices by applying a battery of econometric methods (including hedonic pricing models, spatial regression models, quantile regression models, and a geographically weighted regression model) to 5185 observations in the housing market in Xiamen Island, China. The results of this study are: (1) BRT accessibility premiums and proximity penalties simultaneously exist in the housing market; (2) buyers of high-priced housing have a greater willingness to pay for avoiding the nuisances attributed to proximity to the BRT corridor; (3) the effect of BRT on housing prices is spatially heterogeneous; (4) the BRT accessibility effect is larger in suburban areas than in urban areas; and (5) housing prices are more predictable near the city centers than outside the area, which may be because a greater proportion of the price of a house near the city centers is derived from the location (rather than the building structure). Finally, policy implications (e.g., building acoustic barriers and planting vegetation along the BRT corridor and improving the transit service in suburban areas) are discussed.